A pilot study of stored low titer group O whole blood + component therapy versus component therapy only for civilian trauma patients. Issue 4 (October 2021) - Siletz, Anaar E.; Blair, Kevin J.; Cooper, Richelle J.; Nguyen, N. Charity; Lewis, Scott J.; Fang, Amy; Ward, Dawn C.; Jackson, Nicholas J.; Rodriguez, Tyler; Grotts, Jonathan; Hwang, Jonathan; Ziman, Alyssa; et al.
Abstract : BACKGROUND: This pilot assessed transfusion requirements during resuscitation with whole blood followed by standard component therapy (CT) versus CT alone, during a change in practice at a large urban Level I trauma center. METHODS: This was a single-center prospective cohort pilot study. Male trauma patients received up to 4 units of cold-stored low anti-A, anti-B group O whole blood (LTOWB) as initial resuscitation followed by CT as needed (LTOWB + CT). A control group consisting of women and men who presented when LTOWB was unavailable, received CT only (CT group). Exclusion criteria included antiplatelet or anticoagulant medication and death within 24 hours. The primary outcome was total transfusion volume at 24 hours. Secondary outcomes were mortality, morbidity, and intensive care unit- and hospital-free days. RESULTS: Thirty-eight patients received LTOWB, with a median of 2.0 (interquartile range [IQR] 1.0-3.0) units of LTOWB transfused. Thirty-two patients received CT only. At 24 hours after presentation, the LTOWB +CT group had received a median of 2, 138 mL (IQR, 1, 275–3, 325 mL) of all blood products. The median for the CT group was 4, 225 mL (IQR, 1, 900–5, 425 mL; p = 0.06) in unadjusted analysis. When adjusted for Injury Severity Score, sex, and positive Focused Assessment with Sonography for Trauma, LTOWB +CT group patients received 3307 mL of blood products, and CT group patients received 3, 260 mL in the first 24 hours ( p = 0.95). The adjusted median ratio of plasma to red cells transfused was higher in the LTOWB + CT group (0.85 vs. 0.63 at 24 hours after admission; p = 0.043. Adjusted mortality was 4.4% in the LTOWB + CT group, and 11.7% in the CT group ( p = 0.19), with similar complications, intensive care unit-, and hospital-free days in both groups. CONCLUSION: Beginning resuscitation with LTOWB results in equivalent outcomes compared with resuscitation with CT only. LEVEL OF EVIDENCE: Therapeutic (Prospective study with 1 negative criterion, limited control of confounding factors), level III. Abstract : Supplemental digital content is available in the text.